Appraisal of Factors Influencing Domestic Water Consumption in Urban Areas: The Case of Lokoja Town, Kogi-State, Nigeria - Abenu, Abigail; Abenu, Moses Yaba (Journal of Sustainability and Environmental Management, 2025)
This paper investigates domestic water consumption patterns based on socio-economic factors: monthly income, household size and water rate. A multi-stage sampling technique was employed for the household survey in Lokoja town, which has planned and unplanned neighbourhoods. First, nine neighbourhoods were selected from the twenty-two, and then individual households were selected. The household survey was carried out using a structured interview schedule. The survey results from the 482 selected households revealed that domestic water consumption varied across the sampled neighbourhoods. Domestic water consumption was higher among residents of planned neighbourhoods than among those in unplanned neighbourhoods. Socio-economic factors- household size, monthly income and water rate exerted considerable influence on domestic water consumption. More equitable potable water distribution should be implemented by the government and residents.